EFFICIENCY OF FISHING GEARS AND THEIR EFFECTS ON FISH BIODIVERSITY AND PRODUCTION IN THE CHALAN BEEL OF BANGLADESH - Sayeed, Md. Abu; Hashem, Shaharior; Salam, M. A.; Hossain, Mostafa Ali Reza; Wahab, M. A. (European Scientific Journal, ESJ, 2014)
A study was conducted to provide an overview on the aquatic resources and fisheries status of the Chalan beel and to identify the opportunities for improvement of the existing fisheries management strategies, focusing on fish biodiversity conservation. The Chalan beel is the largest and important watershed in the Northern Bangladesh which covers an area of about 400 km2 during the wet season. Sampling for Catch Assessment Surevey (CAS), Fishing Effort Survey (FES) and watersediment was carried out at the Gumani, the Katagang and the Baral sites. Interview and Focus Group Discussions (FGDs) were conducted in ten upazilas in and around Chalan beel. The most abundant fish species were punti (Puntius sophore and Puntius ticto) followed by chanda (Chanda nama and Parambassis ranga), tengra (Mystus vittatus) and chapila (Gudusia chapra). The abundance of several species showed decreasing trend from 2007 to 2008. The number of professional fishers has declined by 58% between 1982 and 2008 and the fishers left the profession due to much decreased fish availability in the beel as a result of very low fish catch and falling income. A total of 34 different types of fishing gears including nets (11), traps (11), hook and lines (4), wounding gears (4), Fish Aggregating Devices (FADs) (3) and hand-fishing (1) were observed. Seine nets were the dominant gear followed by gill nets and set bag nets. The mean Catch Per Unit Effort (CPUE) of different fishing gears varied widely ranging from 2.04 to 48.99 kg unit−1 day−1. The average total annual fish production of the beel was 12,566.57 MT having average fish production of 281.86 kg ha-1 during the study period. If present trend of fish catching of Chalan beel legally and illegally continues without proper management and control measures, then one of the most valuable aquatic resources of Bangladesh – the Chalan beel would soon be empty of all kinds of fishes. It is the obligation of concerned GOs, NGOs and the people of the country to control the gear efficiency in the Chalan beel and provide alternative livelihood options to the resource-poor fishers of the beel along with other measures for sustainability of the Chalan beel - a major fish reservoir of the country.